2020
DOI: 10.1007/s10493-019-00460-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the potential distribution of Amblyomma americanum (Acari: Ixodidae) infestation in New Zealand, using maximum entropy-based ecological niche modelling

Abstract: Although currently exotic to New Zealand, the potential geographic distribution of Amblyomma americanum (L.), the lone star tick, was modelled using maximum entropy (Max-Ent). The MaxEnt model was calibrated across the native range of A. americanum in North America using present-day climatic conditions and occurrence data from museum collections. The resulting model was then projected onto New Zealand using both present-day and future climates modelled under two greenhouse gas emission scenarios, representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
(102 reference statements)
0
13
0
Order By: Relevance
“…Our results thus highlighted the importance of considering the environment around the sampling point for a good variables estimation in species distribution model, while single point is commonly considered (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Our results also showed that the time period considered before the sampling date, with sliding windows, has a significant impact on the performance of the resulting models.…”
Section: On the Importance Of Considering The Spatial And Temporal Scmentioning
confidence: 55%
See 1 more Smart Citation
“…Our results thus highlighted the importance of considering the environment around the sampling point for a good variables estimation in species distribution model, while single point is commonly considered (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Our results also showed that the time period considered before the sampling date, with sliding windows, has a significant impact on the performance of the resulting models.…”
Section: On the Importance Of Considering The Spatial And Temporal Scmentioning
confidence: 55%
“…These data summarized climatic conditions from 1950 to 2000. Therefore, in these studies as in many others (36)(37)(38)(39)(40)(41)(42)(43)(44) environmental data were extracted at a resolution that did not match the species ecology and more importantly the environmental conditions at sampling dates. Our goals were thus first to build a model of higher spatial resolution (100 m) for Switzerland and second to use recent climatic data to characterize in detail the distribution of Ixodes ricinus and its associated Chlamydiales bacterial pathogen over Switzerland from 2009 to 2019.…”
Section: Considering the Potential Threat To Human Health Caused By Pmentioning
confidence: 99%
“…Moreover, values (probability) from maximum entropy model were predicting impacts by ticks from land use (development) using present tick distribution and environment data (Braunisch et al, 2008). Therefore, we con- future conditions at the area of study (Remya, et al, 2015;Raghavan et al, 2020). In fact, the novelty of this study involves using maximum entropy to predict the horseshoe crab spawning grounds over a large area (c.a.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ENMevaluate result of ΔAICc (delta akaikae information criterion adjusted for small sample size) which is equal to 0 was chosen. ΔAICc has been used by several authors to select the best possible features of environmental layers and to choose the corresponding Regularization multiplier prior to running MaxEnt modeling [1920] [24].…”
Section: Methodsmentioning
confidence: 99%
“…Maximum Entropy (MaxEnt) modeling technique has long been used to model species distribution across the area of interest including disease causing agents and vectors [12][13][14] [ [19][20]. MaxEnt is the preferred method to model species distribution because of its simplicity to employ and can easily extrapolate the current distribution of species in charge into the future projectile climatic scenarios.…”
Section: B Anthracis Distribution Modelingmentioning
confidence: 99%